Penerapan Mesin Pemberi Pakan Ikan Otomatis dan Pelatihan Konsep IoT - Sayuti Rahman; Asmah Indrawati; Andre Hasudungan Lubis (JPM: Jurnal Pengabdian Masyarakat, 2026)
Marindal II Village has considerable potential in the freshwater aquaculture sector; however, it still faces various challenges related to feeding efficiency, high operational costs, and limited adoption of technology. Manual feeding practices often lead to feed waste, irregular feeding schedules, and water pollution in fish ponds. This Community Service Program (PKM) aims to enhance the efficiency and productivity of fish farming through the development and implementation of an automatic fish feeding machine as an initial step toward an Internet of Things (IoT)-based system. The PKM activities were carried out in Marindal II Village in collaboration with the Karang Taruna Youth Group and the PKK community group as partners. The implemented automatic fish feeder is capable of regulating feeding time and dosage in a scheduled manner without manual intervention, thereby reducing feed waste and improving labor efficiency. Although the system has not yet been directly integrated with IoT technology, the design approach and training activities were oriented toward preparing partners for future IoT-based development, such as remote monitoring and sensor integration. Evaluation results indicate improvements in partners’ understanding and skills in managing fish farming activities, feeding time efficiency, and feed waste reduction. This program serves as an important foundation for the sustainable development of IoT-based automatic fish feeding systems in Marindal II Village.